SWOT Analysis on JKN Implementation in Ngaliyan Health Center Semarang in 2016 - Melani, Florentina; Santjaka, Aris; Latif, Rr Vita Nur (Unnes Journal of Public Health, 2018)
ABSTRACT                    The position of  Health Center (Puskesmas) as a first level health facility becomes the spearhead in good implementation of JKN (Jaminan Kesehatan Nasional or National Health Insurance). By using SWOT Analysis in 6M dimension (Men, Money, Method, Material, Machine, Market), it is expected to be an alternative for Ngaliyan Health Center to improve the work performance and become a reliable health facility for Ngaliyan citizens. And it can support the realization of totally covered insurance in 2019. This study aims to explore the strengths, weaknesses, opportunities, and threats to the Ngaliyan Health Center in organizing JKN service in 6M dimension (Men, Money, Method, Material, Market, Machine), to find the critical point and make KSF (Key Success Factor). The research is qualitative descriptive with structured in-depth interview approach. Using 15 informants selected by purposive sampling. The results of this study obtained a critical point that is on the dimension of money. There was a deficit between capitation and expenditure funds of the Health Center in the implementation of JKN.   ABSTRAK                    Kedudukan puskesmas sebagai fasilitas kesehatan tingkat pertama menjadi ujung tombak pelaksanaan JKN yang baik. Dengan menggunakan Analisa SWOT dalam dimensi 6M (Men, Money, Method, Material, Machine, Market) diharapkan menjadi alternatif bagi puskesmas ngaliyan untuk meningkatkan prestasi kerja dan menjadi fasilitas kesehatan yang diandalkan bagi warga Ngaliyan. Serta bisa mendukung terwujudnya totally covered di tahun 2019. Penelitian ini bertujuan untuk mengeksplorasi Kekuatan, Kelemahan, Peluang, dan  Ancaman bagi puskesmas Ngaliyan dalam menyelenggarakan pelayanan JKN dalam dimensi 6M (Men, Money, Method, Material, Market, Machine), untuk menemukan titik kritis, serta membuat FKK (Faktor Kunci Keberhasilan). Penelitian berupa kualitatif deskriptif dengan pendekatan wawancara mendalam terstruktur. Menggunakan 15 orang informan yang dipilih secara purposive sampling.Hasil penelitian ini didapatkan titik kritis yaitu pada dimensi money. Terdapat defisit antara dana kapitasi dan biaya yang dikeluarkan puskesmas dalam pelaksanaan JKN.